Development of a new wet gravity separator with jet flow - Ijichi, Ryota; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2014)
The recycling of post-consumer wastes, such as automobiles, computers and household wastes, is becoming increasingly important in today's world. There are various processing methods of solid wastes, such as jigs, spirals, dense medium separation and magnetic/electrical separation. In the jig, the separation of materials of different specific gravity is accomplished by a pulsating current of water [1]. Although jig separation is one of the oldest solidsolid separation methods, it is the widely used method in coal preparation even today. The jig separation is often applied to utilize the solid waste. In this study, a new continuous wet gravity separator was developed, applying a similar principle of jig separation; i.e. particles are subjected intermittently to an upstream field. The design of the new separator are compact and simple.